Peningkatan Keterampilan Bahasa Anak dalam Komunikasi Melalui Media Boneka Tangan - Vina Rahmatika; Nurul Ismaiyah; Masruroh Masruroh; Ummu Kulsum; Syarif Hidayatulah; Diah Meilani Silvita; Jannatul Munawarah (LP3M STAI MA'ARIF MAGETAN, 2025)
The aim of this study is the improvement of children's language skills in communication through hand puppet media in group A of RA As-Syuhada' Pamekasan. The problem behind the research is the low communication skills of the children, which is indicated by the lack of confidence in public speaking, difficulty in expressing opinions, and limited ability to interact with peers. This research method is a classroom action research (PTK) in two cycles. The research subjects were 37 children in group A. Data collection was done through observation, documentation and anecdotal records. The research instrument included an observation sheet. The results showed a significant improvement from cycle I to cycle II. In Cycle I, only 30% of the children reached the minimum criteria of